Pengaruh Model Problem Based Learning dengan Metode Eksperimen dan Diskusi Terhadap Hasil Belajar Fisika Ditinjau dari Sikap Ilmiah Siswa Kelas X MIPA SMA N 1 Mataram - Muhamad Khairul Azmi; Satutik Rahayu; Hikmawati Hikmawati (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2016)
This study aims to determine: (1) the effect of problem based learning models with experimental methods and discussion on learning outcomes; (2) the effect of Scientific Attitude of students towards learning outcomes; (3) the interaction between the model problem based learning with experimental methods and discussion with scientific attitude of students towards learning outcomes. This type of research is an experimental research study design with Factorial Design 2 x 2. Population in research of all X grade student of MIPA at SMA Negeri 1 Mataram academic year 2015/2016. Sampling studies using cluster random sampling, and get class X MIPA 4 as an experimental class I and class X MIPA 7 as experimental class II. The researchÃ¢â¬â¢s instrument used was a multiple choice test with five alternative answers and considering the validity, reliability, power and the level of difficulty depending matter and using scientific attitude questionnaire instrument. This research showed that the average value of posttest experimental class I was 76.50 and the experimental class II at 79.83 with the average value of the value of the scientific attitude to the experimental class I was 52.42 and 50.70 of the experimental class II. Data obtained beforehand tested normality and homogeneity, earned both classes of normally distributed and homogeneous, then followed by hypothesis testing using analysis of variance (ANOVA) with two different cell. The results of this study show that: (1) There is effect problem based learning model with experimental methods and discussion on learning outcomes; (2) Scientific Attitude effected on the student learning outcomes; (3) There is no interaction between the problem based learning model with experimental methods and discussion with scientific attitude towards learning outcomes.